HUBUNGAN PARITAS DAN SUMBER INFORMASI DENGAN PENGETAHUAN IBU HAMIL TENTANG TANDA BAHAYA KEHAMILAN - Fransisca, Lidya; Adriani; Darmawati, Junay (LPPM STIKes Mitra Adiguna, 2025)
Maternal Mortality Rate (MMR) is one indicator of the success of maternal health programs. Pregnant women's knowledge of danger signs in pregnancy is very necessary because it can help reduce maternal mortality. The purpose of this study was to determine the relationship between parity and sources of information with pregnant women's knowledge of danger signs in pregnancy. The research method used in this study was an analytical survey with a cross-sectional approach. The population in this study were all pregnant women who underwent ANC at RB ASRI Palembang in 2024 with a research sample of 30 respondents taken using the accidental sampling technique. The results of the study were obtained from 30 respondents who had good knowledge 66.7%, high parity 73.3% and those who had received information 66.7%. The results of the chi square test showed that there was a significant correlation between parity (?value 0,041) and sources of information (?value 0,028) with pregnant women's knowledge of danger signs in pregnancy. The advice given is expected so that health workers, especially midwives, can improve IEC about danger signs in pregnancy starting when the mother first undergoes ANC